The entrepreneurial leadership practices of Malaysian secondary school principals in fundraising - Ghazali, Siti Sabihah; Krauss, Steven Eric; Abdul Kadir, Suhaida; Asimiran, Soaib (Sage Publications, 2020)
The reduction of funding allocation for school operations occurs in the education administration yearly. It is a notable fact that schools around the world are facing challenges in school funding as it affects the school’s operation. As a result, the performance of school for the long term would not be a primary concern in the future. Schools in Malaysia are not exempted from this issue as it is one of the main concerns in the centralized schools of this country. Generally, as the number of schools is increasing and a corresponding decrease takes place in centralized funding, it is vital for school principals to find alternatives for fundraising. Following a growing pattern of decentralization of school policies, entrepreneurial leadership currently begins to make an appearance in the education system through the transformation it creates in schools. However, there is insufficient discussion regarding the practices of entrepreneurial leadership and the abilities of entrepreneurial leaders in centralized schools. This study aims to identify the practices performed by centralized school principals to implement entrepreneurial activities in two schools selected for this study, which consisted of two different demographic backgrounds, districts, and locations. It investigates the entrepreneurial leadership practices performed by the Malaysian school principals in fundraising activities. The roles of the school principals as entrepreneurial leaders were identified based on their peers and other school staff who gained the experience of working under those principals. The various fundraising practices of the entrepreneurial leaders of both schools are examined within this crucial and challenging environment, followed by a discussion of how the school administrations deal with the external parties to obtain school funding. This study contributes to the field of educational administration by analysing the current fundraising practices of entrepreneurial principals of centralized schools in Malaysia.